Energy‐aware load adaptive framework for LTE heterogeneous network. Issue 9 (25th April 2014) - Abdulkafi, Ayad Atiyah; Chieng, David; Kiong, Tiong Sieh; Ting, Alvin; Koh, Johnny; Ghaleb, Abdulaziz M.
ABSTRACT One of the main approaches for improving the network energy efficiency (EE) is through the introduction of load adaptive techniques, where the network's components/subsystems are switched off when the network is lightly loaded. Optimising such a dynamic operation in a heterogeneous network (HetNet) remains an active topic of research. In this paper, a traffic load‐adaptive model that aims to evaluate the EE of base stations in Long Term Evolution (LTE) HetNet is presented. First, a model that simulates the load‐adaptive power consumption behaviour of LTE HetNet is developed. In this regard, a load adaptation factor is introduced to assess the network's EE performance. The model also adapts and predicts the achievable data rate of each base station with respect to the traffic load. Our study shows that the fully load‐adaptive LTE HetNet can significantly improve network's EE up to 10%, 40%, and 80% for high, medium, and low loads, respectively, as compared to the conventional non load‐adaptive HetNet. In addition, we show that the full adaptive network operation can achieve significant EE gains under a realistic daily traffic profile up to 86%. The proposed evaluation model is essential to assess the network EE and can be used in future studies that focus on improving the adaptation level of the already installed network equipments. Copyright © 2014 John Wiley & Sons, Ltd.